Loneliness, Stress, Self Esteem and Depression Among Malaysian Adolescents (Jurnal Kemanusiaan, 2017)
ABSTRACT The current study examined the degree of relationships between loneliness, stress and selfesteem with depression among adolescents. The respondents were 1407 secondary school adolescents aged between 13 to 17 years old from selected states in Malaysia. Data were collected by using a self-administered questionnaire. Adolescent depression was measured by Children Depression Inventory (CDI) (Kovacs, 1985) while stress was measured by Perceive Stress Scale (Cohen, 1983). Revised UCLA Loneliness Scale (Russell, Peplau, & Cutrona, 1980) measured loneliness and Rosenberg Self-Esteem Scale (Rosenberg, 1965) measured self-esteem. The findings of the study showed that loneliness, stress and self-esteem have moderate significant relationships with depression and stress emerged as the strongest predictor of adolescent depression.